Effects of EU illegal logging policy on timber-supplying countries: A systematic review. (1st February 2023) - Polo Villanueva, Fredy D.; Tegegne, Yitagesu T.; Winkel, Georg; Cerutti, Paolo Omar; Ramcilovic-Suominen, Sabaheta; McDermott, Constance L.; Zeitlin, Jonathan; Sotirov, Metodi; Cashore, Benjamin; Wardell, David Andrew; Haywood, Andrew; Giessen, Lukas
Abstract: The EU's Forest Law Enforcement, Governance and Trade Action Plan (FLEGT) adopted in 2003 includes bilateral trade agreements known as Voluntary Partnership Agreements (VPAs) signed between the EU and timber-supplying countries. The EU has invested more than 1.5 billion euros in VPAs; however, only one of the seven concerned countries has managed to complete all the necessary requirements to expire FLEGT licences. Since there is no research that comprehensively integrates the scientific evidence regarding the effects of this policy, this study systematically reviews all empirical scientific studies on the effects of VPAs. We found that almost all relevant studies are case reports that use qualitative data and focus on only one country at a time, mainly Ghana, Cameroon, or Indonesia. The evidence suggests that while VPAs have contributed to the establishment of governance structures, tools, and procedures they have not been able to solve social problems (i.e., inequality and injustice) and have potentially harmed the economies of EU timber suppliers. Evidence on the effects of VPAs on illegal logging and trade and the environment remains limited. Thus, future research should focus on more countries; use a greater range of methods, including comparative experimental designs; explore possible intended effects on under-researched categories; and systematically investigate unintended effects on other categories within and outside the forestry sector. Highlights: We reviewed the literature on the effects of FLEGT Voluntary Partnership Agreements. These are bilateral trade agreements between the EU and timber-supplying countries. Most studies are case reports using qualitative data, focusing on one country at a time. VPAs can contribute to the establishment of governance structures tools, and procedures. VPAs are not able to solve social problems and can even harm the economy.